Letter: cytokeratin‐18 as a biomarker of hepatocellular carcinoma regression after transarterial chemoembolization. Authors' reply. Issue 1 (2nd December 2016) - Bantel, H.; Wandrer, F.; Bock, B.; Kirstein, M. M.; Schulze‐Osthoff, K.
Abstract : Linked Content This article is linked to Bock et al and He et al papers. To view these articles visithttps://doi.org/10.1111/apt.13578 andhttps://doi.org/10.1111/apt.13820 .